2012
DOI: 10.4174/jkss.2012.82.3.135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopy-assisted and totally laparoscopic Billroth-II distal gastrectomy for gastric cancer

Abstract: PurposeIn laparoscopic distal gastrectomy for gastric cancer, most surgeons prefer extra-corporeal anastomosis because of technical challenges and unfamiliarity with intra-corporeal anastomosis. Herein, we report the feasibility and safety of intra-corporeal Billroth-II anastomosis in gastric cancer.MethodsFrom April 2004 to March 2011, 130 underwent totally laparoscopic distal gastrectomy with intra-corporeal Billroth-II reconstruction, and 269 patients underwent laparoscopy-assisted distal gastrectomy with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
4
15
0
1
Order By: Relevance
“…But morbidity especially anastomosis leakage were more prevalent in our study. The ratio of anastomosis leakage in other reports ranges from 0 to 4.0% 3,6,12. The oncologic outcomes including proximal resection margin, number of harvested lymph nodes and lymph node station were comparable with the data of large volume centers 3,4,6,12.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…But morbidity especially anastomosis leakage were more prevalent in our study. The ratio of anastomosis leakage in other reports ranges from 0 to 4.0% 3,6,12. The oncologic outcomes including proximal resection margin, number of harvested lymph nodes and lymph node station were comparable with the data of large volume centers 3,4,6,12.…”
Section: Discussionsupporting
confidence: 72%
“…Also, many authors have reported that intracorporeal anastomosis of the TLDG wound be feasible and safe 6,12. In this study, there was no significant difference in operation time, estimated blood loss, or surgical complication between LADG and TLDG.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…However, these issues were not observed when we performed the intra-corporeal anastomosis. Lee et al23 also reported that the intracorporeal Billroth II anastomosis time of TLDG was statistically shorter than that of LADG.…”
Section: Discussionmentioning
confidence: 96%
“…When a tumor has invaded the pyloric canal or duodenum, Billroth-II anastomosis can be performed to achieve R0 resection [ 25 ]. In distal gastrectomy, two-thirds to three-quarters of the distal stomach should be resected, including the distal gastric body, antrum, pylorus, and proximal duodenal bulb.…”
Section: Reconstruction Of the Digestive Tract After Distal Gastrectomymentioning
confidence: 99%